Treatment of HIV-Infected Individuals with the Histone Deacetylase Inhibitor Panobinostat Results in Increased Numbers of Regulatory T Cells and Limits Ex Vivo Lipopolysaccharide-Induced Inflammatory Responses - Christel Rothe Brinkmann (American Society for Microbiology, 2018)
ABSTRACT Histone deacetylase inhibitors (HDACi) modulate the transcriptional activity of all cells, including innate and adaptive immune cells. Therefore, we aimed to evaluate immunological effects of treatment with the HDACi panobinostat in HIV-infected patients during a clinical phase IIa latency reversal trial. Using flow cytometry, we investigated changes in T cell activation (CD69, CD38, HLA-DR) and the expression of CD39 and CTLA4 on regulatory T cells (Tregs). Whole-blood stimulations were performed and cytokine responses measured using Luminex. Gene expression in purified peripheral blood mononuclear cells (PBMCs) was evaluated using an Affymetrix HTA 2.0 gene chip. We found that proportions of CD4+ and CD8+ T cells expressing CD69 increased 24 h after initial panobinostat administration (P < 0.01), followed by an increase in the proportions of CD38+ HLA-DR+-coexpressing CD4+ T cells on day 4 (P = 0.02). Concurrently, proportions of Tregs increased by 40% (P = 0.003). Treg CTLA4 median fluorescent intensity (MFI) increased by 25% (P = 0.007), and CD39 MFI on CD39+ Treg increased by 12% (P = 0.02). Lipopolysaccharide (LPS)-induced inflammatory responses (interleukin-1β [IL-1β], IL-6, IL-12p40, and tumor necrosis factor alpha [TNF-α]) in whole blood were significantly downregulated 4 days after initial dosing. Lastly, panobinostat induced significant changes in the overall gene expression pattern (fold change, >1.5; false-discovery-rate [FDR]-corrected P, <0.05). Importantly, measures of immune function returned to baseline after panobinostat treatment and follow-up revealed no sustained effect on overall gene expression. IMPORTANCE The effect of treatment with histone deacetylase inhibitors on the immune system in HIV-infected individuals is not clear. Analysis of results from a clinical trial in which 15 HIV-infected individuals received 12 doses of panobinostat identified a significant impact on both T cell activation status and regulatory T cell suppressive marker expression and a reduced level of monocytic responsiveness to inflammatory stimuli. These changes were substantiated by global gene expression analysis. Collectively, the results suggest that panobinostat has multiple effects on innate and adaptive immune responses. Importantly, all the effects were transient, and further panobinostat treatment did not cause persistent long-term changes in gene expression patterns in HIV-infected individuals.